Tanggung Jawab Bank Terhadap Nasabah yang Dananya Terbukti Digunakan oleh Karyawan Bank - Lintar Bagas Putra Efrianto; Diana Wiyanti (Jurnal Riset Ilmu Hukum, 2022)
Abstract. Customers are an important factor in banking, therefore to gain customer trust, banks must be accountable for their business activities to customers. This study aims to identify and analyze the bank's responsibility for the loss of customer funds that were intentionally used by bank employees and to determine the legal considerations of the Supreme Court judges in this case. The research method used is normative juridical research, namely research that analyzes bank responsibilities and Supreme Court decisions by examining secondary data consisting of primary legal materials and secondary legal materials. The theory used is the theory of legal protection and the theory of responsibility to answer the main problem. Based on the results of the study, it is known that the bank is not responsible for returning customer funds that are proven to be used by bank employees. Based on the provisions of Article 10 of PBI Number 16/1/2014 concerning Consumer Protection and Article 29 of POJK Number 1/POJK.07/2013 concerning Consumer Protection in the Financial Services Sector, the bank must be responsible for consumer losses arising from the negligence of its management and employees. For this incident, the customer sued the bank to court to get the funds back. Abstrak. Nasabah adalah faktor penting dalam perbankan, oleh karena itu untuk mendapatkan kepercayaan nasabah, bank harus mempertanggungjawabkan kegiatan usahanya kepada nasabah. Penelitian ini bertujuan untuk mengetahui dan menganalisis tanggung jawab bank atas hilangnya dana nasabah yang dengan sengaja digunakan oleh karyawan bank dan untuk mengetahui pertimbangan hukum majelis hakim MA atas kasus tersebut. Metode penelitian yang digunakan adalah penelitian yuridis normatif, yaitu penelitian yang menganalisis tanggungjawab bank dan Putusan MA dengan cara meneliti data sekunder yang terdiri dari bahan hukum primer dan bahan hukum sekunder. Teori yang digunakan adalah teori perlindungan hukum dan teori tanggung jawab untuk menjawab pokok permasalahan. Berdasarkan hasil penelitian diketahui bahwa pihak bank tidak bertanggungjawab mengembalikan dana nasabah yang terbukti digunakan oleh karyawan bank. Berdasarkan ketentuan Pasal 10 PBI Nomor 16/1/2014 Tentang Perlindungan Konsumen dan Pasal 29 POJK Nomor 1/POJK.07/2013 Tentang Perlindungan Konsumen Sektor Jasa Keuangan, pihak bank wajib bertanggung jawab atas kerugian konsumen yang timbul akibat kelalaian pengurus dan pegawainya. Atas peristiwa tersebut nasabah menggugat bank ke pengadilan untuk mendapatkan kembali dananya